A Tolsztoj-szövegek sajátos természete fordítói szemmel: A Tolsztoj-fordítások problematikája az orosz és a magyar nyelv különbözőségei alapján - Molnár, Angelika (Studia Litteraria, 2024)
In the following essay I discuss the linguistic-cultural aspects and editorial problems of the new translations of Leo Tolstoy’s certain works which determine the interpretation of A Prisoner of the Caucasus, Aer the Ball, e Sevastopol Sketches, Russian Books of Reading, War and Peace, Anna Karenina. £e literary translation course launched for master’s students at the Institute of Slavic Studies of the University of Debrecen, the Center for Russian Language, and Regional Linguistic Studies of Leo Tolstoy Tula State Pedagogical University have been cooperating for several years in the project Language Poetics of Leo Tolstoy’s Works. An important place among the various areas of the project is occupied by the linguistic commentary of the writer’s classical texts, which aims to make them accessible to today’s young readers. The problems of Tolstoy translations based on the specific nature of his texts and the differences between Russian and Hungarian are demonstrated through the examples analyzed in this project.